Energy-Efficient Hybrid Secured Routing For 5g Vehicular Ad Hoc Network (Vanet) - Zerihun, Tamiru (ASTU, 2021)
These days, road accidents and traffic jams have increased significantly on the route due to the higher number of vehicles. Vehicular Ad hoc Networks (VANETs) are effective intelligent transportation systems in decreasing accidents and traffic congestions. Vehicular communications deal with not only information about traffic and road conditions but also involved user-specific information such as their route and time-critical information. However, the information transmission is vulnerable to eavesdropping and link failure due to the high mobility of the vehicles. In this research, analysis of Secured Routing to provide information to the legitimate nodes in the presence of unwanted eavesdroppers is done. The hybrid energy-efficient routing algorithm is used for better stability of the connected vehicle. The beamforming technique is applied to prevent the eavesdropper from intercepting confidential information using an array of antennas. A combined detailed analytical model of min norm DoA, LMS adaptive beamforming, hybrid route based on Dijkstra and Bellman Ford algorithm showed a greater secrecy rate. The simulation is carried out in MATLAB 2014a MEX file package software. The result obtained such as energy efficiency and secrecy rate are convincing compared to the previous result content in the literature.
Keywords: Vehicular Ad hock Network (VANET), Secured Routing, LMS, Min norm